Korelasi Jumlah Streptococcus mutans (S. mutans) dan Level Ekspresi Interlukin 8 (IL-8) pada Severe Early Childhood Caries - Muhammad Luthfi; Retno Indrawati; Ira Arundina; Yoes Prijatna Dachlan (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Correlation of Streptococcus mutans (S. mutans) Level and Interleukin 8 (IL-8) Expressions of Salivary Neutrophils in Severe Early Childhood Caries. Early childhood caries is a very serious health problem because it is a chronic infectious disease that is contagious. Dental caries begins after the primary teeth grow and develop on the tooth surface very quickly and progressively. In recent years the views of neutrophils have changed dramatically. Neutrophils not only act as a microbe killer through phagocytosis, the release of reactive oxigen species (ROS) and its antimicrobial peptide, but neutrophil activation also helps regulate the immune response. To analyze the relationship between the amount S. mutans and IL-8 expression of salivary neutrophils in severe early Childhood caries. Two groups, namely Isolation of S. mutans were performed on saliva samples taken from 20 caries-free and 20 severe early childhood caries and samples Nacl 1,5% mouthwash results of 20 caries-free and 20 severe early childhood caries salivary neutrophils that were analysis of IL-8 expression by flow cytometry. Based on the average value, it is known that S. mutans level in early Childhood caries-free is lower (513.500,00 +185.565,28 CFU/ml) in comparison to the severe early Childhood caries (977.000,00 +222.500,15 CFU/ml), but the expression of IL-8 neutrophil salivary neutrophils in early Childhood caries-free is higher (3,31+0,50) in comparison to the severe early Childhood caries (2,95+0,56). The increased S. mutans level is probably caused by the decrease in the expression of IL-8 salivary neutrophils in severe early childhood caries.